2005
DOI: 10.1007/s10461-005-3895-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Brief Scale to Measure AIDS-Related Stigma in South Africa

Abstract: Although there has been progress in AIDS stigma research, there are no multi-item AIDS stigma scales that have been shown reliable and valid in Africa. The current research reports the development of the nine-item AIDS-Related Stigma Scale. Research conducted in five South African communities (N = 2306) found the scale internally consistent, alpha = 0.75 and time stable over 3 months, r = 0.67. The scale was also reliable in three different languages (English, Xhosa, and Afrikaans). Correlations showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
317
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 338 publications
(338 citation statements)
references
References 13 publications
13
317
2
1
Order By: Relevance
“…In the present study, no significant relationship was found between Attitudes toward HIV/AIDS and WTP in a future HIV vaccine trial among adolescents in the \Vestern Cape. A possible reason for this null finding is that the AIDS-related Stigma Scale (Kalichman et al, 2005) used in the present study was not reliable in the adolescent sample. The guidelines offered by Nunally (1978) suggest that a reliability of 0.70 or higher is acceptable for scales used in beginning research.…”
Section: 5mentioning
confidence: 56%
See 2 more Smart Citations
“…In the present study, no significant relationship was found between Attitudes toward HIV/AIDS and WTP in a future HIV vaccine trial among adolescents in the \Vestern Cape. A possible reason for this null finding is that the AIDS-related Stigma Scale (Kalichman et al, 2005) used in the present study was not reliable in the adolescent sample. The guidelines offered by Nunally (1978) suggest that a reliability of 0.70 or higher is acceptable for scales used in beginning research.…”
Section: 5mentioning
confidence: 56%
“…The Internal consistency analysis of the AIDS-related Stigma Scale (Kalichman et al, 2005) revealed a Cronbach alpha reliability of a = 0.49. After deleting two items, the internal consistency improved (a =0 .60).…”
Section: 5mentioning
confidence: 99%
See 1 more Smart Citation
“…Стигматизирующее отношение приводит к отрицанию риска и снижению вероятности принятия норм поведения, предотвращающих инфициро-вание [17,18]. Страх перед стигмой [15,19] и стигматизи-рующие убеждения -которые закрепляют представление о том, что ВИЧ поражает только других людей -удерживают людей от прохождения тестирования на ВИЧ [19] в самых разных обстоятельствах.…”
Section: низкая обращаемость за услугами по профилактике вич и тестирunclassified
“…Items used in this short scale were derived from Kalichman et al (2005) and Bhagwanjee (2008). (Bhagwanjee, 2008).…”
Section: Stigmamentioning
confidence: 99%